Gestational Trophoblastic Neoplasia: A Clinico-Epidemiological Profile In A Tertiary Care Hospital - Das, Indrani; Mandal, Payel; Samanta, Sandip; Mistri, Pallab Kumar; Kyal, Amit; Mukhopadhyay, Partha (Birat Journal of Health Sciences, 2022)
Introduction: Gestational trophoblastic neoplasia (GTN) is a group of interrelated lesions that results from abnormal proliferation of placental trophoblastic cells. Early diagnosis and treatment of GTN results in successful outcomes with fertility preservation.This study was intended to stratify GTN cases using WHO scoring system, to diagnose and manage cases as per protocol and to identify complications of treatment of GTN. Methodology: This was a single center prospective observational study conducted at Medical college Kolkata from June 2017 to December 2018. All the diagnosed cases of GTN fulfilling the inclusion criteria were incorporated in the study, data were collected from history, clinical examination and investigations. All the data were tabulated and analyzed by standard statistical methods Results: In this study, primiparous are more prone to have GTN and molar pregnancy was the commonest antecedent event (71.4% of cases). 74.3% (26 out of 35) patients developed disease within four months of previous pregnancy. Anemia and vaginal bleeding were the presenting symptoms in >48.0% cases whereas hemoperitoneum,seizure, hemoptysis and respiratory distress were the rare presenting symptoms.In this study, the cases were diagnosed by histopathology or serial estimation of serum β-hcg. In our study, 91.4% patients were successfully treated with methotrexate and only three cases received EMACO. Conclusion: To conclude this study established that cases of GTN can be successfully treated by early diagnosis and timely management.